2016
DOI: 10.1016/j.envpol.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, distribution and seasonal variation of organophosphate flame retardants and plasticizers in urban surface water in Beijing, China

Abstract: a b s t r a c tThe occurrence, spatial distribution and seasonal variation of 14 organophosphate esters (OPEs) were investigated in urban surface water (river and lake water) from July 2013 to June 2014 in Beijing, China. Sewage influent and effluent samples, as well as rainwater and road runoff samples were also analyzed as the potential sources of OPEs in surface water. Tris(2-chloro-1-methylethyl) phosphate (TCPP) and tris(2-chloroethyl) phosphate (TCEP) were the most abundant OPEs with the average concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(83 citation statements)
references
References 46 publications
(91 reference statements)
8
73
2
Order By: Relevance
“…where RQ is the risk quotient, MEC is the measured environmental concentration, PNEC is the predicted no effect concentration, LC 50 is the lethal concentration required to kill 50%, EC 50 is the concentration of a toxicant which induces a response halfway between the baseline and maximum after a specified exposure time, and f is the security factor. For RQ calculations, the lowest L(E)C 50 for fish, Daphnia and algae associated with TCEP, TCPP, TDCPP, TPP and TDBPP and a factor of 1 000 were used (EC, 2003;Cristale et al, 2013;Shi et al, 2016). Table 1 presents the acute toxicity used for risk assessment.…”
Section: Rq = Mec/ Pnecmentioning
confidence: 99%
See 1 more Smart Citation
“…where RQ is the risk quotient, MEC is the measured environmental concentration, PNEC is the predicted no effect concentration, LC 50 is the lethal concentration required to kill 50%, EC 50 is the concentration of a toxicant which induces a response halfway between the baseline and maximum after a specified exposure time, and f is the security factor. For RQ calculations, the lowest L(E)C 50 for fish, Daphnia and algae associated with TCEP, TCPP, TDCPP, TPP and TDBPP and a factor of 1 000 were used (EC, 2003;Cristale et al, 2013;Shi et al, 2016). Table 1 presents the acute toxicity used for risk assessment.…”
Section: Rq = Mec/ Pnecmentioning
confidence: 99%
“…In the same study, a TCEP range of 119-316 ng/L was observed, which was similar to the results obtained in our study. Concentration ranges of 38-3 700 ng/L were reported from Songhua River, China (Wang et al, 2011). Shi et al (2016 reported ranges of < LOD-2 072 ng/L (mean 291 ng/L) and < LOD-855 (mean 46.3 ng/L) for TCEP and TDCPP in surface water from Beijing respectively.…”
mentioning
confidence: 99%
“…The mixture was stirring at 45 C for 6 h. Then the mixture was settled in the liquid separating funnel aer neutralizing with sulfuric acid solution. The upper compounds were washed with acid solution and distilled water.…”
Section: Synthesis Of Tung Oil Methyl Estermentioning
confidence: 99%
“…Pure PVC is with stiff backbone and high glass transition temperature (T g ) at around 90 C. The addition of plasticizer into the PVC polymer will increase distance of PVC chains and make macromolecule structure polymer easy to move, increasing free volume of polymer and reducing T g . [43][44][45] The substituting of chlorine atoms with aminated tung oil methyl ester will increase distance between PVC chains and reduce intermolecular force. An internal plasticization will be expected to reduce T g of PVC materials.…”
Section: Property Of Self-plasticizing Pvc Materialsmentioning
confidence: 99%
“…Since the phasing-out of polybrominated diphenyl ethers (PBDEs) in 2005, the production and use of TDCIPP has been increased and it can now be detected across the globe in various environments, such as indoor air in the US (up to 56.08 mg/g) (Stapleton et al, 2009) and in China (14.3e40.1 mg/g) (Yang et al, 2013;He et al, 2015), surface water (855 ng/L; Shi et al, 2016), and biota samples (e.g., freshwater fish: 89 ng/g lipid wt; Hallanger et al, 2015). TDCIPP or its major metabolite [bis (1, 3-dichloro-2-propyl) phosphate, BDCIPP] has also been detected in human breast milk (5.1 ng/g lipid wt; Sundkvist et al, 2010), urine (11 ng/ ml; Butt et al, 2014), and placenta (82.8 ng/g lipid wt; Ding et al, 2016).…”
Section: Introductionmentioning
confidence: 99%